Working Capital Management on Dividend with Profitability as a Mediation Variable - Rosdiana, Rosdiana; Husaen, Tamrin (KAMBOTI: Jurnal Sosial dan Humaniora, 2022)
Working capital management is the management of a number of assets in the company's daily activities whose aim is to earn profit, therefore its management is very important in the company in order to provide the maximum rate of return in the form of dividends to investors. The purpose of this study is to analyze the effect of working capital management on dividends, to analyze the effect of working capital management on profitability, and to analyze the effect of working capital management on dividends through profitability. This study uses manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2020 period as many as 55 companies so that the number of observation data is 110 data. The type of data in this research is quantitative research using purposive sampling technique and the instrument used in this research is financial statements. The results show that working capital management has a positive effect on dividend policy, working capital management as proxied by cash turnover cycles has a negative effect on profitability, but receivables turnover and inventory turnover cycles have a positive effect on profitability. In an indirect relationship, it was found that the cash turnover cycle had a negative effect on dividends through profitability, but the receivable turnover cycle and inventory turnover cycle had a positive effect on dividends through profitability. Therefore, the conclusion in this study is that working capital management has a positive effect on dividend policy and profitability, but indirectly working capital management which is proxied by the cash turnover cycle has a negative effect on dividend policy through profitability.